Probiotic Supplements and Food Products: Comparison for Different Targets - Neda Mollakhalili Meybodi; Amir Mohammad Mortazavian; sara Sohrabvandi; Adriano G da Cruz; Reza Mohammadi (Applied Food Biotechnology, 2017)
Background and Objective: Currently, probiotics are mainly used in processed foods or nutritional supplements mainly due to their impact on health. The probiotic markets have a considerable share either in food or drug industry. In this article, drug supplements and food products containing probiotic microorganisms are considered in a comparative approach from different aspects including functional, efficacy, hedonistic and economical. Results and Conclusion: However, the impact of ingesting probiotics via food products or drug supplements is not actually the same from consumer’s point of view as well as from clinical efficacy. Consumer attitudes appear to be reflected in expectations on nutritional, functional and health effects side and also from the point of nutrition economics. Conflict of interest: The authors declare no conflict of interest.